Mycobacterium abscessus—An Emerging True Pathogen: A Case Report - Shruti Appaswamy; Bhavesh D Rathod (Pediatric Infectious Disease)
Infections caused by nontuberculous mycobacteria (NTM) are increasing globally and are notoriously difficult to treat due to their intrinsic resistance to many commonly used antibiotics. NTM are diverse and ubiquitous in the environment, with only a few species causing serious and often opportunistic infections in humans, including Mycobacterium abscessus. It is one of the commonly identified NTM species responsible for severe respiratory, skin, and mucosal infections in humans and is often regarded one of the most antibiotic-resistant mycobacteria, leaving us with few therapeutic options. Although historically known to cause infections in immunocompromised individuals, the incidence of infections in immunocompetent humans is on the rise, giving it the status of a true pathogen. This is a case report of an 18-month-old child diagnosed in an urban secondary care center with M. abscessus soft tissue infection, which was acquired postimmunization. Microbiological evidence was consistent with multidrug-resistant strains of M. abscessus. The child was evaluated for primary and secondary immunodeficiencies and was started on appropriate treatment based on culture and sensitivity, that is, linezolid and amikacin, which led to the resolution of the infection. Prevention of these infections at the source level is of utmost importance. Since the organisms are frequently found on hospital instruments, water sources, and surfaces, timely and regular sterilization and microbiological quality checks should be carried out.